Framework for 2D animation jitter - Lee, Pui Kuan. (2012)
Animation has a long and rich history that allows animators the freedom to do anything. It has changed in many ways by experimentation and innovation to reach what it is today through using computer animation technology. Traditional animation is one of the animation techniques. In traditional animation process, each of the frames was drawn one at a time by hand before it can be individually tape as a frame of film. As each of the drawings will differ slightly from the one before it, a jitter effect is produced when the frames are animated at a rapid rate.